2020
DOI: 10.3390/ncrna6030033
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Non-Coding RNA in Depression and Bipolar Disorder: Can They Be Used as Diagnostic or Theranostic Biomarkers?

Abstract: The similarities between the depressive symptoms of Major Depressive Disorders (MDD) and Bipolar Disorders (BD) suggest these disorders have some commonality in their molecular pathophysiologies, which is not apparent from the risk genes shared between MDD and BD. This is significant, given the growing literature suggesting that changes in non-coding RNA may be important in both MDD and BD, because they are causing dysfunctions in the control of biochemical pathways that are affected in both disorders. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 146 publications
(177 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, miRNAs were also identified as potential biomarkers of BD, schizophrenia (Amoah et al, 2019;Fries et al, 2018), MDD (Gururajan et al, 2016), suicidal behaviour in BD patients (Squassina, 2020), and nausea intensity in MDD patients treated with mood stabilizers (Yrondi et al, 2020). Altogether, these results suggest that miRNAs may be potential diagnostic and predictive biomarkers in psychiatric disease (Gibbons et al, 2020).…”
Section: Micro-rnasmentioning
confidence: 85%
“…Furthermore, miRNAs were also identified as potential biomarkers of BD, schizophrenia (Amoah et al, 2019;Fries et al, 2018), MDD (Gururajan et al, 2016), suicidal behaviour in BD patients (Squassina, 2020), and nausea intensity in MDD patients treated with mood stabilizers (Yrondi et al, 2020). Altogether, these results suggest that miRNAs may be potential diagnostic and predictive biomarkers in psychiatric disease (Gibbons et al, 2020).…”
Section: Micro-rnasmentioning
confidence: 85%
“…Therefore, any disruption or imbalance in the expression and function of miRNA networks could lead to neurological diseases and, in fact, there is accumulating evidence that miRNAs have been implicated in neurological disorders such as Parkinson's disease (PD), Alzheimer's disease (AD) and major depression disorder (MDD) (19)(20)(21). Thus, expression changes in specific miRNAs could serve as potential biomarkers for diagnostic or therapeutic targets in clinical practice (22). However, the underlying mechanisms of miRNAs in contributing to the development and progression of these neurological disorders, in particular depression, remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that overexpression or disorder of miRNAs is associated with the occurrence and development of many complex diseases 10 , including neurological diseases such as Parkinson's disease, Alzheimer's disease and major depressive disorder 11 . Variations in speci c miRNAs have potential as biomarkers for diagnostic or therapeutic targets in clinical practice 12 . However, the mechanisms by which miRNAs contribute to the development and progression of these neurological disorders, especially depression, remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%